Artistic and Aesthetic Formation and Evolution of Architectural and Urban Planning Space - Bulakh, І.V. (Наука та інновації, 2019)
Introduction. The chaotic and random development of urban space is typical for all cities of Ukraine and for the majority of cities of the world. This phenomenon is caused by progressive urbanization, globalization, internationalization, commercialization, and pop culture of the urban planning environment. Problem Statement. The neglect of urban context, regional features of the territories, and historical palimpsest layers of building sites, as well as the domination of material values over intellectual enrichment are the reasons for the lack of artistic and aesthetic idea of the urban environment. Purpose. The purpose of this research is to systematize the existing knowledge on symbolization in the context of the creation of artistic image of urban environment and to define the principles of symbolization. Materials and Methods. Comparative analysis, structural and logical modelling, systematization of research results, literary and informational sources, and experimental design methods. Results. The urban environment is considered a hierarchical multilayer system that gradually integrates 4 (global, macro, local, and micro) levels. The formation of architectural and urban artistic image consists of four stages: the search of analogies, the schematic expression of similarity, the abstraction with the help of allegory, and the creation of a symbol through giving a new content to the sum of abstract ideas. The communicative, transformative, commutative, and metamorphic principles of symbolization have been proposed. Conclusions. Among the segmental postmodern ideas of modern city images, environmental concepts, and scientific directions of the studies of urban formation there is one common thing that is the perception of city as a complex, open, and dynamic system. The city artistic image, while developing and expanding in space and time, covers all the levels of formation of architectural and urban environment, which are interconnected by a variety of images of urban planning, architectural compositions of buildings and structures into a single integrity full of symbolic sense. Вступ. Хаотичність і невпорядкованість нової забудови міського середовища спостерігається в усіх містах України та в більшості міських поселень світу. Цьому явищу сприяють прогресуючі урбанізація, глобалізація, інтернаціоналізація, комерціалізація, попкультурність середовища міських планувань. Проблематика. Основою проблемного кола відсутності художньо-естетичного осмислення міського середовища є нехтування міського контексту, регіональних особливостей територій, історичних палімпсестних нашарувань ділянок забудови, пріоритет матеріальних цінностей над духовним збагаченням. Мета. Систематизація наявних знань у галузі символізації художнього образотворення міського середовища, визначення принципів символізації. Матеріали й методи. Порівняльний аналіз, структурно-логічне моделювання, систематизація результатів наукових досліджень, літературних та інформаційних джерел, методи експериментального проектування. Результати. Міське середовище розглядається як ієрархічна багатошарова система, що поступово інтегрує чоти ри складові рівні: глобальний, макрорівень, локальний та мікрорівень. Процес формування архітектурно-містобудівного художнього образу складається з чотирьох стадій образотворення: пошук аналогій, схематичне вираження подібності, абстрагування за допомогою алегорії, створення символу шляхом надання нового змісту сумі абстрагованих ідей. Запропоновано принципи символізації: комунікативність, трансформативність, комутативність та метаморфічність. Висновки. Серед розрізнених постмодерністських уявлень про образи сучасного міста, середовищних концепцій та наукових напрямів дослідження міських утворень об'єднуючим є сприйняття міста як складної, відкритої та динамічної системи. Художній образ міста, розвиваючись і розгортаючись в просторі й часі, охоплює всі рівні формування архітектурно-містобудівного середовища, які поєднані між собою багатоманітними образами міського розпланування, архітектурних композицій будівель і споруд в єдину цілісність, наповнену символічним змістом. Введение. Хаотичность и неупорядоченность новой застройки городской среды наблюдается во всех городах Украины и в большинстве городов мира. Этому явлению способствуют прогрессирующие урбанизация, глобализация, интернационализация, коммерциализация, попкультурность городской среды. Проблематика. Отсутствие художественно-эстетического осмысления городской среды связано с пренебрежением городским контекстом, региональными особенностями и историческими палимпсестными наслоениями территорий, приоритетом материальных ценностей над духовным обогащением. Цель. Систематизация существующих знаний в области символизации художественного образа городской среды, определение принципов символизации. Материалы и методы. Сравнительный анализ, структурно-логическое моделирование, систематизация результатов научных исследований, литературных и информационных источников, методы экспериментального проектирования. Результаты. Городская среда рассматривается как иерархическая многослойная система, постепенно интегрирующая четыре уровня: глобальный, макроуровень, локальный и микроуровень. Процесс формирования архитектурно-градостроительного художественного образа состоит из четырех стадий: поиск аналогий, схематическое выражение сходства, абстрагирование с помощью аллегории, создание символа путем предоставления нового содержания сумме абстрактных идей. Предложены принципы символизации: коммуникативность, трансформативность, коммутативность и метаморфичность. Выводы. Среди разрозненных постмодернистских представлений об образах современного города, средовых концепций и научных направлений исследования городских образований объединяющим является восприятие города, как сложной, открытой и динамичной системы. Художественный образ города, развиваясь и разворачиваясь в пространстве и времени, охватывает все уровни построения архитектурно-градостроительной среды, связанные между собой многочисленными образами городских планировок, архитектурных композиций зданий и сооружений в единую целостность, наполненную символическим содержанием.